(untitled) (Research, Society and Development, 2021)
The discharge of domestic sewage is one of the most common types of marine pollution, namely through submarine outfalls. In this study, water and sediments of the coastal submarine sewage outfall in Guarujá, São Paulo, Brazil were assessed during the high (January) and low (April) tourist seasons in 2018. The Canadian Council of Ministers of the Environmental Water Quality Index (CCMEWQI) showed a “marginal” water quality, in both seasons, where dissolved oxygen, biochemical oxygen demand, oil and greases, ammonia, surfactants, aluminium, lead, copper, nickel, Escherichia coli and Enterococci showed potential ecological risks. However, no mutagenic potential was detected in the complex mixture (Ames Salmonella/microsome test: MI<2), and no protozoa and Salmonella bacteria were found. In the sediment, a total of 25 benthic taxa were inventoried, suggesting that the macrofauna is not under contamination stress. Cadmium, lead, copper, chromium, nickel and zinc were below the Threshold Effect Level, and the Geoaccumulation Index was <0. Furthermore, the absence of acute toxicity to the test organism Kalliapseudes schubartii (EC50: 96h) and the Shannon-Wiener diversity index (H’: 2.5 to 3.5 bits/ind) suggests healthy or unpolluted environments. However, the deviation of some environmental indicators suggests the need of continuous monitoring based on field measurements.